Evaluation of the efficiency and safety of tocilizumab therapy in patients with systemic-onset juvenile idiopathic arthritis: results of a retrospective follow-up - M. M. Kostik; E. A. Isupova; I. A. Chikova; M. F. Dubko; V. V. Masalova; L. S. Snegireva; O. V. Kalashnikova; V. G. Chasnyk (Современная ревматология)
Objective: to study the efficiency and safety of tocilizumab (TCZ) therapy in patients with systemic-onset juvenile idiopathic arthritis (sJIA). Patients and methods. The retrospective study included 48 children with active sJIA in whom TCZ therapy was initiated because of the inefficiency of using different anti-rheumatic drugs. The investigators studied the time course of changes in the main indicators of sJOA activity, as well as the possibility of achieving remission in accordance with the Wallace criteria (2004). Results and discussion. The main demographic characteristics of the study group (median [25th and 75th percentiles]) included the age of the patients (9.9 [5.0; 12.7] years) and the duration of TCZ therapy (27.0 [5.9; 89.7] months). 40 (83.3%) patients achieved remission; the median of its achievement was 138.5 [56.0; 255.0] days. The patients who had achieved remission had milder sJOA: hepatosplenomegaly, pulmonary and cardiac involvements, and macrophage activation syndrome were less frequently observed. At baseline, they also had higher hemoglobin values and a lower erythrocyte sedimentation rate, and decreased levels of leukocytes, granulocytes, C-reactive protein (CRP), lactate dehydrogenase (LDH) and ferritin. The main predictors for achieving remission, which were estimated using the analysis of sensitivity and specificity, as well as Cox regression models, were CRP ≤82.0 mg/l (OR – 7.9; HR – 1.17); ESR ≤32 mm/h (OR – 17.0; HR – 0.85), ferritin ≤273 ng/ml (OR – 56.5; HR – 2.6), hemoglobin >113 g/l (OR – 17.0; HR – 1.33), LDH ≤676 U/l (OR – 113.6; HR – 3.2), platelets >335⋅109 /l (OR – 5.0; HR – 2.5), and a decline in white blood cells two weeks after the first infusion by more than 11% (OR – 13.0; HR – 6.0) and in granulocytes by more than 12% (OR – 14.0; HR – 4.7). Conclusion. Children with a less severe course of sJIA more promptly reached remission during TCZ therapy. Male gender, high inflammatory activity, previous glucocorticoid therapy, long time to achieve remission, and TCZ dosing regimen deviations were the main factors for an exacerbation of sJOA. Male sex, signs of the high disease activity, preceding CS treatment, long time to achievement of inactive disease and treatment protocol deviations increased risk of sJIA flare.